Cities, Aggregate Welfare, and Growth - Katja Gehr; Michael Pflüger (CESifo GmbH, 2025)
This paper explores the macroeconomic consequences of regulatory barriers in housing markets. We take a European perspective, allowing us to offer novel facts, theory, and methodology. Our focus is on Germany, a compelling case exemplifying key characteristics unique to European city systems. To take our model to the data, we estimate its structural equations for the population elasticities of urban benefits and costs using rich micro-data. The quantified model receives strong support from several sources of independent evidence. We study the effects of a counterfactual reduction of land-use regulations on aggregate welfare and evaluate the effect of cities on growth.
Keywords: C52; R12; D24; 330; city systems; urban growth; urban benefits and costs; land-use regulations; amenities; location fundamentals